Current surgical treatment of diverticular disease in the Netherlands - Morks, Annelien N (Baishideng, 2010)
AIM: To evaluate the development of diagnostic tools, indications for surgery and treatment modalities concerning diverticular disease (DD) in the Netherlands. METHODS: Data were collected from 100 patients who underwent surgery for DD in three Dutch hospitals. All hospitals used the same standardized database. The collected data included patient demographics, patient history, type of surgery and complications. Patients were divided into two groups, one undergoing elective surgery (elective group) and the other undergoing acute surgery (acute group). RESULTS: Two hundred and ninety-nine patients were admitted between 2000 and 2007. One hundred and seventy-eight patients underwent acute surgery and 121 patients received elective operations. The median age of the 121 patients was 69 years (range: 28-94 years), significantly higher in acute patients (P = 0.010). Laparoscopic resection was performed in 31% of elective patients. In the acute setting, 61% underwent a Hartmann procedure. The overall morbidity and mortality were 51% and 10%, and 60% and 16% in the acute group, which were significantly higher than in the elective group (36% and 1%). Only 35% of the temporary ostomies were restored. CONCLUSION: This study gives a picture of current surgical practice for DD in the Netherlands. New developments are implemented in daily practice, resulting in acceptable morbidity and mortality rates.